Mapalus In Educational Leadership - Theo Chanra Merentek; Shelty Deity Meity Sumual; Paulus Robert Tuerah; Welky Karauwan (research, training and philanthropy institution Natural Aceh, 2023)
Abstract: Mapalus is the philosophy of life for the people of Minahasa, North Sulawesi, in the general sense of mutual cooperation. This study aims to describe Mapalus' relationship with types, styles, principles, and principles in educational leadership. This study uses library research methods (library research). Data was collected through books, literature, references, and articles related to Mapalus and Educational Leadership. The results showed that Mapalus, which contains the principles of kinship, cooperation, and religion with the principles of mutual assistance, openness, discipline, and togetherness, has a relationship with democratic leadership, free leadership, charismatic leadership, paternalistic leadership, expert leadership, visionary leadership, and moralist leadership, but not has a relationship with authoritarian leadership because it is not in accordance with the principles and principles of Mapalus. Meanwhile, the principles and principles of Mapalus have a very close relationship with educational leadership.